2016
DOI: 10.1177/0020852316641494
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of public–private partnership in Ireland: a sustainable pathway?

Abstract: Ireland is a latecomer to Public Private Partnership (PPP) having only adopted it in 1998.Prior to the credit crisis, Ireland followed the UK model with PPPs being implemented in transport, education, housing/urban regeneration and water/wastewater. Having stalled during the credit crisis, PPP has been reactivated recently with the domestic infrastructure stimulus programme i . The focus of this paper is on Ireland as a younger participant in PPP and the nexus between adoption patterns and sustainability chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A recent study by Sheppard & Beck (2016) has contended that, while Ireland's central government originally introduced the UK's PPP model as a voluntary option to modernize its public administration, it is now increasingly pushing the adoption of PPPs for infrastructure delivery. Ireland's public-sector organizations are now reported as reluctantly pursuing PPPs simply to maintain institutional legitimacy (Sheppard and Beck, 2016). Moreover, Jooste, Levitt, and Scott (2011) have found that mimetic pressures explain the diffusion of infrastructure PPPs from the UK into British Columbia (Canada), Victoria (Australia), and South Africa.…”
Section: Isomorphic Pressures and Adoption Of Pppmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Sheppard & Beck (2016) has contended that, while Ireland's central government originally introduced the UK's PPP model as a voluntary option to modernize its public administration, it is now increasingly pushing the adoption of PPPs for infrastructure delivery. Ireland's public-sector organizations are now reported as reluctantly pursuing PPPs simply to maintain institutional legitimacy (Sheppard and Beck, 2016). Moreover, Jooste, Levitt, and Scott (2011) have found that mimetic pressures explain the diffusion of infrastructure PPPs from the UK into British Columbia (Canada), Victoria (Australia), and South Africa.…”
Section: Isomorphic Pressures and Adoption Of Pppmentioning
confidence: 99%
“…The same study revealed that, while Ireland's local government knew about the "negative aspects of PPPs in the UK," they still "persisted with the PPP model and sought legitimacy through its adoption" (p. 12). Interestingly, Sheppard and Beck (2016) contend that, while Ireland's central government originally introduced the UK's PPP model as a voluntary option to modernize its public administration, it is now increasingly pushing the adoption of PPPs for infrastructure delivery. Ireland's public-sector organizations are now reported as reluctantly pursuing PPPs to maintain institutional legitimacy (Sheppard and Beck, 2016).…”
Section: Isomorphic Pressures and Adoption Of Pppmentioning
confidence: 99%
See 1 more Smart Citation
“…b E.g., the phrase ' … transports policy, transfer of passengers' was discovered as 'policy transfer'. c Five papers, however, proved to advance a moderate engagement with policy movement (Anderson & Collins 2014;Blessing 2016, Osypuk 2015, Van Vliet 2003 or housing (Sheppard & Beck 2018). For full reference, see the Annex.…”
Section: S7mentioning
confidence: 99%
“…The nature and evolution of the relationship between government and NPOs will be understood both in terms of governmental nonprofit funding and in terms of governmental control (Verscheure & Corte 2010). Prior to the financial crisis, many Western countries implemented publicprivate partnership models in diverse areas (Sheppard & Beck 2016). For instance, a PPP related to infrastructure may involve a complex set of parties (Jooste & Scott 2012).…”
Section: Cross-sector Partnershipsmentioning
confidence: 99%